A Comparative Study of Specific Phase based Character Recognition Techniques for Various Scripts - Solanki, B; Ingle, M (International Journal of Computer Sciences and Engineering, 2025)
Character recognition creates an increasing demand on various evolving applications areas and methodologies of image processing in order to effectively recognize text of each script. It is considered as common method of digitizing an image in order to gather text of image more efficiently. The stages of character recognition include pre-processing, segmentation, feature extraction, classification and post processing. It has been noticed that there exist numerous languages such as Marathi, Gujarati, Gurumukhi, Arabic, Modi etc. where stages of character recognition lays important role for recognition of text image. Pre-processing and segmentation are considered as two crucial stages of character recognition with the purpose of providing smooth and clean image for further processing. These stages help in enhancing color format, to maintain skew angle of images, compresses size of image, separates line word and characters from images etc. A comparative study of various sub stages of pre-processing and segmentation is performed based on some parameters such as data type, window size, recognition rate, sample size, and so on. These parameters help in improving quality of image in order to achieve successful recognition rate